Practical Evaluation Method for the Pouring Scheme of a Long-Span Concrete-Filled Steel Tube Arch Bridge - Xinyu Yao; Tianzhi Hao; Nianchun Deng (Advances in Civil Engineering)
Concrete pouring steel tube arch is a critical part in the construction of a long-span concrete-filled steel tube arch bridge. With the adoption of the improved TOPSIS, this study summarized five indicators that controlled the concrete-filled steel tube pouring sequence. The indicators include the vertical displacement of the arch rib, lateral offset of the arch rib, steel tube stress, concrete stress, and elastic safety factor of the arch rib. Furthermore, a comprehensive objective function-rationalization index was proposed, based on which a practical evaluation and determination method for pouring scheme of the long-span concrete-filled steel tube arch bridge was developed. The results showed that a pouring sequence with relatively small stress in the arch rib, advanced alignment, and good stability could be determined using the proposed method.